Impact of technologies during COVID-19 pandemic for improving behavior intention to use e-learning - Tawafak, R. M.; AlFarsi, G.; Jabbar, J.; Malik, S. I.; Mathew, R.; AlSidiri, A.; Shakir, M.; Romli, A. (International Association of Online Engineering, 2021)
COVID-19 pandemic has adversely affected the whole world. Its impact on the education sector cannot be considered small. This study aims to explore the roles and effects of Technology-Enhanced Learning (TEL) in assisting pedagogy, abolishing technophobia among undergraduates, to overcome the pandemic and to prevent the near-total closure of education. The study conducted among undergraduate students. The smart learning practices ofMiddle East countries and TEL effectiveness of using Google meet, online communication, Blogging, PDF reports and presentation, free teaching and learning applications in enhancing behaviour intention of learning also enclosed in the article as innovative solutions. The effectiveness, challenges and recommendations of the e-learning system studied. The results revealed that the features of TEL spur and encourage the behaviour intention to use e-learning and technologies. The results show how the adoption of TEL helped to overcome the global lockdown of educational institutions which might have affected the student’s future.